Preliminary validation of the Satisfaction With Decision scale with depressed primary care patients - Wills, Celia E. (Health Expect, 2003)
Objective To conduct a preliminary validation of the Satisfaction With Decision (SWD) scale with depressed primary care patients. Design  Cross‐sectional observational pilot study using a postal survey. Setting and participants  Depressed primary care patients (n = 97) who recently had made a new decision about antidepressant medication use completed surveys regarding their treatment decisions. Main variables  Measures included patient‐reported satisfaction with decision, decisional conflict, knowledge about depression and treatment, decision involvement, pain and health status, antidepressant medication efficacy, and satisfaction with health services. Results  The SWD scale had good internal consistency reliability (α = 0.85). Evidence for construct validity was confirmed via a hypothesized pattern of relationships between the SWD scale and other measures. Decision satisfaction was associated with several issues of relevance for designing patient‐centred decision support interventions: (1) knowledge about depression and treatment; (2) involvement in health‐related decisions; and (3) aiding evaluation of trade‐offs among pros and cons of treatment. Conclusions  The results of this pilot study show that the SWD scale appears to be a psychometrically sound and practical measure for research with this population. Additional research is needed on the theoretical nature of decision satisfaction and developing and testing patient‐centred decision support interventions for depression treatment.